Implementasi JASBESKAPMERAH Sebagai Inovasi Layanan di Dinas Perpustakaan dan Kearsipan Kabupaten Ngawi - Anggrainy, Khalisa; Handayani, Nurul Setyawati (Perpustakaan Nasional, 2025)
Libraries have entered a new era where libraries are no longer just a place to store books, but can also support education by providing services and information. To meet user needs, libraries need to make various innovations based on current circumstances. This is realized by the Ngawi Regent's Library and Archives Office through the JASBESKAPMERAH service innovation. This study aims to determine the implementation and constraints of JASBESKAPMERAH services at the Ngawi Regency Library and Archives Office. The type of research is descriptive with a qualitative approach method. The data collection technique is three ways: participatory observation, semi-structured interviews, and documentation. Data analysis techniques in qualitative research are applied when data collection is carried out within a certain period by reducing data, presenting data, and drawing conclusions. The results of this study indicate that the implementation of JASBESKAPMERAH services has a target, namely elementary school students who are quite enthusiasm about participating in various activities, one of which is free shuttle, ANBK simulation using computers, and historical memory activities. The obstacles that occur are the lack of facilities and infrastructure, limited time, and historical reminiscence activities that have not been carried out optimally.